EARLY MIOCENE INSULAR VERTEBRATES FROM LAERRU (SARDINIA, ITALY): PRELIMINARY NOTE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
A new vertebrate assemblage was discovered in an Early  Miocene lacustrine deposit near the village of Laerru (northern Sardinia, Italy). The assemblage is composed by mammals, reptiles and a bird. The mammals are represented by three ruminants (cf. Sardomeryx oschiriensis, Pecora indet. small size and Pecora indet. very small size) and one dormouse (Peridyromys aff. murinus) while reptiles are represented by turtles (Trionychidae?) and crocodiles (cf. Diplocynodon sp.). A bird bone fragment is also reported and referred to Palaeortyx cf. brevipes (Galliformes). The assemblage can be related to the “Oschiri fauna”, one of the oldest endemic insular fauna known in the Mediterranean. The age of the Laerru vertebrates is early-middle Burdigalian, between 18.8 and 18.3 Ma, corresponding to the mammal unit of the main land MN3. The predominance of ruminants confirms the good capacity of these mammals to colonize insular environments.